Institutional Strengthening of Academic-Based Cooperatives: Results of a Cross-Disciplinary Replication Study in Malaysia - Indrayani, Tri Irfa; Helmayuni; Lusi Utama; Sevindrajuta; Asmawati; Zuherna Mizwar (Journal of Community Service and Application of Science, 2025)
International community service (PKM) is a tangible form of university involvement in strengthening academic-based cooperative institutions. This activity was carried out through collaboration with ANGKASA Kuala Lumpur, the parent organization of cooperatives in Malaysia, which has long experience in the development of modern cooperatives. Community Service (PKM). This study involves the fields of economics, law, health, and technology, to identify best practices in the institutional management of cooperatives in higher education The purpose of the activity is to increase the capacity of cooperatives of universities in Indonesia through multidisciplinary synergy, covering the fields of economics, law, health, and technology. The implementation method includes literature studies, field observations, Focus Group Discussions (FGD), and the preparation of cooperative internationalization action plans. The results show that university cooperatives in Indonesia still face challenges in the form of limited governance, lack of innovation in business units, and low utilization of digital technology. Through collaboration with ANGKASA, a model of strengthening cooperatives, developing preventive health business units, implementing governance according to modern legal principles, and integrating digital technology for member services was obtained. In conclusion, international PKM is a strategic step to encourage Indonesian university cooperatives to be globally competitive. The findings show that cooperative digitalization systems, cross-field institutional integration, and strengthening of internal regulations are the foundations for the success of cooperatives in Malaysia. It provides strategic recommendations in strengthening the institution of academic cooperatives in Indonesia